The other side of the story lived experiences of adolescent siblings of people with anxiety and/or mood disorders - Del Rosario, Bea Lucille C.; Matawaran, Janille D.
Adolescence is a crucial stage of development, and for those with siblings diagnosed with anxiety and/or mood disorders, this period presents unique challenges. This study investigated the lived experiences of Filipino adolescents aged 17-25 who have siblings diagnosed with anxiety and/or mood disorders. It aimed to understand how these adolescents perceive their roles within the family, their emotional and psychological needs, and the sacrifices they made while navigating their siblings' mental health challenges. It also sought to shed light on the triumphs the well-siblings have made despite the challenges they experienced. Using a qualitative phenomenological approach, semi-structured interviews through zoom and google forms were conducted to gather in- depth narratives from participants. Data were analyzed through reflexive thematic analysis to identify patterns and extract meaningful insights. The data from the findings showed that culture significantly influences their experience. Although they underwent the same experience with their western counterparts, the influence of culture affects the parenting which in turn affects the experience of the child. Ingrained cultural expectations affect how the participants view their situation. The findings were expected to contribute to the limited literature on the impact of mental health disorders, with a particular focus on the experiences of well-siblings in the Filipino context, a population often overlooked in writing.